Criminal Responsibility of the Perpetrator of Obstruction of Justice in Corruption Crimes - Aryani, Esti; Jumiati, Agatha; Pamungkas, Nova Satria (Indonesian Journal of Law and Justice, 2025)
This research aims to examine the criminal liability of obstruction of justice perpetrators in corruption offenses and analyze the existence of regulations on obstruction of justice in current and future legislation.This research is a normative legal study that uses a case study approach, involving the examination of specific cases from various legal aspects. The case approach is conducted by examining cases related to the issues faced that have become court decisions with permanent legal force. In the case currently under examination, the defendant Friedrich Yunadi, who is a lawyer, was proven legally and convincingly guilty of the crime of "intentionally and jointly obstructing the investigation against the suspect in a corruption case." The sentence imposed by the First Instance Court was 7 (seven) years and a fine of Rp.500,000,000 (five hundred million rupiah), with the provision that if the fine is not paid, it will be replaced with a prison sentence of 5 (five) months. At the appellate level, the High Court upheld the decision of the Central Jakarta District Court No.9/pid.Sus-TPK/2018/PN.Jkt.Pst dated March 5, 2018. Then, the level of the criminal case imposed on the defendant was revised to a prison sentence of 7 years and 6 months and a fine of Rp.500,000,000.00 (five hundred million rupiah). If the fine is not paid, it will be replaced with an 8 (eight) month prison sentence. The change in punishment is due to the defendant's actions as an Advocate that violated the law, which can damage and erode public trust in the law enforcement profession, especially Advocates.